The Liquid Biopsy: A Detailed Review of Evolution, Technologies and Clinical Implications - Karra Geetha; Gottimukkala Rakshitha; Golusula Yuvaraj; T. Rama Rao (International Journal of Scientific Research in Science and Technology, 2024)
Liquid biopsy has transformed molecular diagnostics by providing a non-invasive method for disease identification and monitoring, notably in cancer. This study examines the history of liquid biopsy, with an emphasis on the critical role of circulating tumor DNA (ctDNA) and the move from targeted to genome-wide analysis. It emphasizes the value of liquid biopsy in non-invasive diagnosis, patient comfort, real-time monitoring, and individualized treatment solutions. Success stories in early cancer identification across several cancer types highlight the efficiency of liquid biopsy in detecting particular genetic alterations associated with early-stage illness. The paper also examines the use of liquid biopsy for tracking treatment response and finding minimum residual disease, underlining its potential to revolutionize therapy assessment and post-treatment care. However, consistency issues, such as heterogeneity in sample collection, storage, and processing, as well as variations among cancer types, represent substantial barriers to the widespread use of liquid biopsy. Efforts to solve these problems through collaborative projects and standardization ideas are presented, with a focus on data sharing and the advancement of innovative liquid biopsy technologies. Overall, this review gives a thorough overview of liquid biopsy achievements and limitations, emphasizing its promise as a foundation for current diagnostic techniques.
Keywords: Liquid biopsy; Circulating tumor DNA; Non-invasive diagnosis; Individualized treatment; Early cancer identification; Precision medicine